Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1590/s0100-84042000000200011
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and other biotic interactions in figs of Ficus eximia Schott (Moraceae)

Abstract: -(Pollination and other biotic interactions in figs of Ficus eximia Schott (Moraceae)). During the period from 1992 to 1997, interactions of several organisms and Ficus eximia figs, a monoecious species, were studied in plants located in Campinas/SP and Londrina/PR (Brazil). Ficus eximia is pollinated by a single fig wasp species, Pegoscapus sp. (Hymenoptera: Agaonidae, Agaoninae), but also visited by other 14 non-pollinating wasps (Agaonidae, Eurytomidae, Torymidae). Mites (Tarsonemidae), nematodes (Diplogast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 46 publications
(49 reference statements)
3
20
0
4
Order By: Relevance
“…The type-material of the type series of most species of Heterandrium is from Blumenau County, State of Santa Catarina, Brazil (Boucek 1993). The species has also been reported on F. eximia Schott in areas of Campinas County, State of São Paulo and Londrina County, State of Paraná by Pereira et al (2000) and on F. clusiifolia Summerh, in the coastal forest of Três Praias, Guarapari County, State of Espírito Santo (Schiffler, unpublished). In this work, specimens from this genus were found in some F. mexiae syconia, thus increasing its distribution to Lavras, Minas Gerais.…”
Section: Schifflermentioning
confidence: 82%
See 2 more Smart Citations
“…The type-material of the type series of most species of Heterandrium is from Blumenau County, State of Santa Catarina, Brazil (Boucek 1993). The species has also been reported on F. eximia Schott in areas of Campinas County, State of São Paulo and Londrina County, State of Paraná by Pereira et al (2000) and on F. clusiifolia Summerh, in the coastal forest of Três Praias, Guarapari County, State of Espírito Santo (Schiffler, unpublished). In this work, specimens from this genus were found in some F. mexiae syconia, thus increasing its distribution to Lavras, Minas Gerais.…”
Section: Schifflermentioning
confidence: 82%
“…This genus possesses eight well-known species in southern Brazil (Boucek 1993). Pereira et al (2000) reported it as occuring on F. eximia in Campinas and Londrina counties. It also occurs on F. clusiifolia in Guarapari County (Schiffler, unpublished).…”
Section: Schifflermentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with studies in the southeast and centre-west of Brazil, it was found that the wasp fauna associated with Amazonian fig trees is more diverse. The wasp community in F. citrifolia in this study comprised 29 species, while in Mato Gross do Sul (Costa and Graciolli 2010), São Paulo and Londrina (Pereira et al 2000), 12 and 15 species were registered respectively. The same was confirmed for F. americana subspecies guianensis form mathewsii which here contained 22 species in comparison with those in the study by Conchou et al (2013) in French Guiana, with just six species.…”
Section: Discussionmentioning
confidence: 52%
“…In the ovaries in which pollen was deposited, seed development occurs, while in the ovaries where the eggs were deposited larvae developed (Weiblen 2002). The fig syconia are also exploited by different groups of organisms that are non-pollinators, such as wasp species of the families Pteromalidae, Torymidae and Eurytomidae (Boucek 1993;Weiblen 2002), since they deposit their eggs from the outside, and other arthropods such as beetles and butterfly larvae, mites and drosophilid flies (Lachaise et al 1982;Bronstein 1988a;Frank & Thomas 1996;Pereira et al 2000;Schifler 2002;Sugiura & Yamazaki 2004).…”
Section: Resumo Insetos Associados Aos Sicônios De Ficus Citrifolia mentioning
confidence: 99%